Phythochemical and biological studies on goniothalamus malayanus - Hamdan, Asfiar (Universiti Malaysia Sarawak (UNIMAS), 2005)
Phytochemical and biological studies have been carried out on the stem bark of COlliol/wlUlIIIlS IIll1lc~\ ·(lI1l1s. In the study, extraction has been carried out using three different rypes of <;olvents; hexane, ethyl acetate and ethanol, followed by thlctionation and puri tication. Ethyl acetate crude ('xtract was subjected to Tl,C analysis and yielded 4 spots with Rr values of' 0.75. 0.81. 0.87 and 0.91 in dichlowmethane-ethyl acetate-acetone (4:2: I) solvent system. For column chromatography, 19 combined Ira tions were obtained. Fraction GCO I was subJected to PTLC analysis ami resulted 3 compounds namely GCOI (i), GCOI (ii) and GCOI (iii) ',.\ith Rr values 01'0.77, 0.90 and 0.93. Compound GCOI (iii) was the most pure compound than GCOI (ii) and GCOI (iii) with the highest peak at retention time or '2_.799 min, Brine shrimp toxicity test performed on crude extracts and lI'actions revealed that crude extracts and ti'actions have low toxicity on Arlemia salina except for fraction GCO I which gave LC -II value of 100 pg/mL.. All the crude extracts also showed moderate toxicity against fungus PI'CI/OP0I'IIS spp. and .\"chi=ophyllunI comrnllne.